2013
DOI: 10.3109/2000656x.2013.800529
|View full text |Cite
|
Sign up to set email alerts
|

Combined usage of intercostal nerve block and tumescent anaesthesia: An effective anaesthesia technique for breast augmentation

Abstract: Patients are occasionally unhappy with the size, shape, and positioning of breast implants. An option to improve their satisfaction with breast augmentation includes directly involving them in the process with awake surgery done under nerve block and tumescence. This study describes the resultsof using such an awake anaesthesia technique in 35 patients. After the intercostal nerves dominating the Th3 to Th6 regions were anaesthetized using 0.5% bupivacaine, a tumescent solution consisting of lidocaine, epineph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…5 Other studies of intercostal nerve block use in breast augmentation have not reported any cases of pneumothorax. 16,25,30 In concordance with the low incidence shown in these previous studies, we encountered only one pneumothorax, which resolved spontaneously and was likely related to simultaneous port placement.…”
Section: Discussionsupporting
confidence: 90%
“…5 Other studies of intercostal nerve block use in breast augmentation have not reported any cases of pneumothorax. 16,25,30 In concordance with the low incidence shown in these previous studies, we encountered only one pneumothorax, which resolved spontaneously and was likely related to simultaneous port placement.…”
Section: Discussionsupporting
confidence: 90%
“… 1 , 2 TLA has been extended to a wide range of other surgical procedures involving cutaneous, subcutaneous, breast, and vascular tissues. 3 25 The maximum safe dosage of tumescent lidocaine for these procedures is unknown. There is a need for a pharmacokinetic-based estimate of the maximum safe milligram per kilogram dosage of tumescent lidocaine.…”
mentioning
confidence: 99%
“…Diclophenac also can be given in combination with nerve block with excellent result. Combined usage of intercostal nerve block and tumescent anaesthesia is an effective anaesthesia technique for breast augmentation [3].…”
Section: Discussionmentioning
confidence: 99%